Main regulations and laws of the school library: Brazil and Amazonas (Práxis Educativa, 2024)
This article aims to provide an overview of Brazilian regulations and legislation pertaining to school libraries in Brazil, with a focus on the state of Amazonas. The methodology adopted involves bibliographic review and documentary analysis, covering from the historical evolution of libraries to current legislation, such as Federal Law no. 12.244/2010, which seeks to universalize libraries in the country’s educational institutions. Despite these initiatives, challenges persist, evidenced by bills in progress. The need to balance adaptation to technological changes while preserving the social and culture of school libraries is highlighted. The article also addresses the influence of libraries on social and political transformations, highlighting the lack of compliance of school libraries with the laws, which require significant improvements to meet educational and cultural demands, especially in public institutionsKeywords: School library. Library legislation. Amazonas.